One-pot integrated processing of biopolymers to furfurals in molten salt hydrate: understanding synergy in acidity. Issue 16 (31st July 2017) - Sadula, Sunitha; Oesterling, Owen; Nardone, Andrew; Dinkelacker, Brian; Saha, Basudeb
Abstract : Developed as energy-efficient and integrated method for soluble sugars and furfurals with high yields and high carbon efficiency from polysaccharides and lignocellulosic biomass. Abstract : The manufacture of furfural and 5-hydroxymethylfurfural (HMF), promising renewable platforms for bio-products, with high carbon efficiency is a challenge because of their undesired polymerization to humins. Here, we present an integrated process in inorganic salt solution to overcome this challenge. First, sugar biopolymers yield high monosaccharides (>90%) via efficient saccharification at low temperature. Second, monosaccharides in hydrolysates undergo efficient dehydration in biphasic solvents, assisted by the Brønsted acidity of the salt solution and the added inorganic Lewis acid. The salt solution exhibits high carbon efficiency in furfural and 5-hydroxymethylfurfural (HMF) products (>80 mol%) when compared with the analogous non-salt systems due to the cooperativity of the dual acidity and the higher viscosity of the salt solution than water and the concurrent reactive extraction of products. The process integration makes the separation of the aqueous phase easy, demonstrating nearly comparative activity upon recycling. Intact lignocellulose also achieves high yields of the dehydration products via one-pot depolymerization and saccharification, followed by dehydration. In addition, we elucidate the reasons for the high saccharification efficiency of the salt solution by correlating the effective acidity from the electrode potential and Hammett acidity measurements.